Probing the Impact of Ionic Liquid Additives at the Buried NiOx/Perovskite Interfaces to Understand Solar Cell Performance - Juan Tirado; Mriganka Singh; Michel De Keersmaecker; Erin L. Ratcliff (Advanced Materials Interfaces)
Abstract The buried interfaces between charge‐selective contacts and metal halide perovskites are critical to photovoltaic device performance, and as such, a number of additives are proposed to control and modify energy level alignment. Interface engineering strategies ultimately require the successful detection of near‐band energetics as well as the assessment of charge transport processes, including injection and/or extraction barriers under relevant electric fields. Herein, the study utilizes a low‐cost, straightforward electroabsorption approach for operando characterization of buried interfaces of NiOx hole‐selective layers/metal halide perovskite photoactive layers, complemented with full solar cell device performance. The spectroelectrochemical approach is used to quickly optimize the functionalization process of nickel oxide nanoparticles (NiOx NPs) with 1‐ethyl‐3‐methyl‐imidazolium iodide (EMIMI) using ITO/NiOx NPs/perovskite half‐stack structures and correlating the transport phenomena with changes in surface chemistry and energetics. The spectroelectrochemical tool proves to be a valuable analytical methodology to study the quality and properties of buried interfaces in perovskite‐based (opto)electronic devices, is agnostic with both hole‐ and electron‐selective contacts, and conceivably extended to other semiconductor junctions, as it allows for quantification of surface effects and can predict device performance under operando conditions.